Estudo dos Doryctinae (Hymenoptera: Braconidae) em áreas de mata da região sudeste brasileira - Pinto, Clóvis Sormus de Castro (Universidade Federal de São Carlos, 2014)
The Hymenoptera parasitoids have great importance in maintaining of the environmental balance in the population control of many insect hosts. For the present study, was made a faunistic survey of Doryctinae from collected at INCT- Hympar Sudeste. Samples were collected in 32 municipalities each one of them with five sampling points, excluding São Luís do Paraitinga city with seven points, all with different sampling efforts. To capture of insects, Malaise, Moericke and swep of vegetation traps were used. The total number of individuals captured was 8,210 specimens, distributed in 32 valid genera, during the period between 2009 and 2011. Jundiaí city had the largest number of specimens of Doryctinae, with 1,411 individuals and occurrence frequency of 17.18%, and also the largest genus richness, with 15 in total. Seven municipalities had a unique genus to the location. Heterospilus Haliday was the dominant genus with 83.11% of the total collected specimens (6,824). The collection method with which most individuals was captured was swep of vegetation with 47.24% of the total Doryctinae collected by this technique (1,239). Although avoidance about 7% of the biome, and to be quite fragmented, the Atlantic Forest concentrated at Southeastern region in Brazil presented very abundant and rich in genus of Doryctinae, being found in this work two of them endemic to the Atlantic Forest: Percnobracon Kieffer and Rimacollus Marsh. Six new species of Hecabolus Curtis, a new species of Lissodoryctes Marsh, and a new species and first record of Nervellius Roman, and three new first records of Megaloproctus Schulz were published during the development of this work.
Keywords: Entomologia; Hymenoptera; Braconidae; Doryctinae; CIENCIAS BIOLOGICAS::ECOLOGIA